2014
DOI: 10.1093/ejcts/ezu166
|View full text |Cite
|
Sign up to set email alerts
|

Results of minimally invasive, video-assisted mitral valve repair in advanced Barlow's disease with bileaflet prolapse†

Abstract: Minimally invasive approach for complex MV repair is feasible and safe and provided excellent early and mid-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The main findings from this study can be summarized as follows. First, MIMVS is a reproducible technique with good outcomes 26‐28 . Second, there was a low incidence of conversion to full midline sternotomy with only three episodes.…”
Section: Discussionmentioning
confidence: 95%
“…The main findings from this study can be summarized as follows. First, MIMVS is a reproducible technique with good outcomes 26‐28 . Second, there was a low incidence of conversion to full midline sternotomy with only three episodes.…”
Section: Discussionmentioning
confidence: 95%
“…53,63 Minimally invasive concomitant double or triple valve surgeries via mini-thoracotomy have been shown to be safe alternatives to sternotomy. 61,62,64 In one highvolume institute, 169 aortic valve replacement surgeries with concomitant mitral valve replacement or repair have been performed over 5.5 years with low morbidity and mortality.…”
Section: Future: Advanced Minimally Invasive Surgerymentioning
confidence: 99%
“…Our studies have shown that meticulous hemostasis was carried out and the protamine is fully reversal with heparin before lobectomy, the occurrence of bleeding complications and incomplete lymph node dissection can be reduced. Our successful one-stage VATS oncologic resection and MIS of the MV resulted in a good clinical and cosmetic outcome, rapid patient recovery, and overall patient satisfaction [5] (Fig. 2d).…”
Section: Discussionmentioning
confidence: 81%